The Jampana Attraction and Collaborative Art Creation of Garut Regency, West Java - Hidayat, Herman; Sarip, Hendi Ahmad; Hasanah, Tita; Habibi, Yudi; Asari, Hasim (Institut Riset dan Publikasi Indonesia (IRPI), 2025)
The Jampana attraction and the creation of traditional arts are collaborative creations that have become the identity of Garut Regency, which we continue to preserve and maintain wholeheartedly. This article aims to examine the novelty of the Jampana attraction and the arts and culture resulting from the process of traditional art creation and creation. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, documentation, and training. Data analysis techniques are carried out using qualitative analysis techniques that include data collection, data reduction, data presentation, and drawing conclusions. Meanwhile, for data validity techniques, the researcher uses data triangulation techniques and methods. The results of this study state that known as stretchers are usually used in various traditional activities, arts and cultural activities, Islamic day activities, and national activities. Each stretcher contains various forms, ranging from agricultural products, forms of identity of each region, sheep, house shapes, fish, and others. This Jampana Attraction Art has many innovations that have been created by the community in accordance with the development of the times and this needs to be preserved to become a cultural heritage that continues to be cared for by various generations. Traditional Collaborative Arts and Creative Arts carried out in the process of creating creative and innovative works involve several arts, namely Gamelang Degung Art, Gamelan Awi Art, Badeng Art, Jampana Dodombaan Art, Traditional Dance Art, Dwiwarna Music Art, Angklung Art, Arumba Art, Raja Dogar Art, Creative Dance Art.